Prevalence of non-suicidal self-injury, suicidal ideation, suicide attempts, suicide mortality in eating disorders: a systematic review and meta-analysis - Amiri, Sohrab; Khan, Moien AB (Eating disorders, 2023)
Eating disorders have a wide and profound impact on psychological and general health. The study aims to provide a comprehensive and up-to-date review of non-suicidal self-injury, suicidal ideation, suicide attempts, and suicide mortality in a variety of eating disorders. A systematic search was conducted using four databases from inception until April 2022, limiting the search to English-language. For each of the eligible studies, the prevalence of suicide-related issues in eating disorders was calculated. The prevalence of non-suicidal self-injury, suicide ideation, and suicide attempts was then calculated for each anorexia nervosa and bulimia nervosa. The random-effects method was used for the pool of studies. Fifty-two articles were used for this study and included in the meta-analysis. The prevalence of non-suicidal self-injury is 40% with a confidence interval between 33-46% (I 2 97.36%). The prevalence of suicide ideation is 51% with a confidence interval between 41-62% (I 2 97.69%). The prevalence of suicide attempts is 22% with a confidence interval between 18-25% (I 2 98.48%). The heterogeneity in the studies included in this meta-analysis was high. There is a high prevalence of non-suicidal self-injury, suicidal ideation, and suicide attempts in eating disorders. Thus, comorbidity between eating disorders and suicide issues is an important topic that can provide insights into etiology. Future studies must consider eating disorders along with other types of mental health issues, such as depression, anxiety, sleep problems, and aggression.